Too many or not enough? A methodology for evaluating fire and gas detector layouts at LNG facilities. Issue 1 (18th June 2021) - Hendrickson, Bryant; Gavelli, Filippo; Piekarz, Jake
Abstract: NFPA 59A Standard for the Production, Storage, and Handling of Liquefied Natural Gas (LNG) requires facilities to have the equipment necessary for the detection and control of fires, leaks and spills of hazardous materials, yet provides no requirements or guidance on the location of the detectors. Literature available in the public domain outlines key factors to consider in developing layouts for flame and gas detectors, but a methodology to use this information in evaluating a hazard detector layout is not clearly defined; instead, generic and non‐quantifiable terminology such as "quick and reliable" is often used. As a result, there is no consistent approach to developing flame and gas detector layouts for land‐based LNG facilities and there is no systematic method for regulators to evaluate these designs. The ability to quantify hazard detector performance and define performance targets are of particular interest to the Department of Transportation (DOT) Pipeline and Hazardous Materials Safety Administration (PHMSA), which regulates numerous LNG facilities in the United States. Blue Engineering and Consulting is working on a DOT‐PHMSA sponsored project to develop a risk‐based approach and criteria for hazard detector layouts at LNG facilities. This project builds upon performance‐based design principles outlined in NFPA 72 National Fire Alarm and Signaling Code and the International Society of Automation (ISA) technical report 84.00.07 Guidance on the Evaluation of Fire, Combustible Gas, and Toxic Gas System Effectiveness . The methodology divides the LNG facility into Detection Areas based on the hazards present and the plant layout, identifies the appropriate hazard scenarios to evaluate the detector layout, establishes performance targets for each Detection Area, and quantifies hazard detector coverage. This paper will describe and demonstrate the proposed methodology. It should be noted that, while performance targets must be chosen for the purposes of the demonstrative included in this paper, these targets should not be interpreted as requirements of DOT‐PHMSA nor as acceptable to them.